Enhancing the mechanical efficiency of skilled rowing through shortened feedback cycles - Harfield, P. (Loughborough University, 2016)
In elite level rowing competition, the average velocities of medallists differ by less than 1 % over 2000 m. Nations place sporting excellence in high regard and this magnifies the importance of success. As a result, sports science and technology is increasingly used to achieve marginal performance gains. This research considers how to advance biomechanical analysis and skills training provision with a particular focus on the technical and practical delivery of real-time feedback to coaches and athletes, thereby shortening the amount of time between feedback cycles. Underpinning any biomechanical feedback intervention, validated determinants of performance are required. Previous research revealed that, while gross biomechanical measures such as athlete power, stroke rate and stroke length have previously been used as key determinants of performance, elite athletes are nowadays performing within expected ranges and therefore it is no longer possible to easily differentiate crews using these measures alone. This thesis describes workshops held with elite coaches to investigate biomechanical efficiency where the outcomes led to a focus on how a boat accelerates and decelerates during a stroke and hence how the boat's velocity fluctuates. Novel metrics are proposed to quantify aspects of a stroke cycle and used to analyse an elite data set, collected using a standardised protocol. It is shown that individual elite rowers can be successfully differentiated and benchmark values of performance are presented. Consideration of previous research suggests that there is currently no suitably functional and flexible biomechanical real-time feedback system to deliver complex skills training in rowing. Therefore, this thesis describes the research that has led to the development and evaluation of new technology to deliver visual and audible interfaces that support the delivery of concurrent and terminal feedback in water and land-based environments. Coaches and athletes were involved throughout the design process to optimise system suitability and encourage adoption. The technology empowers a coach to intricately manipulate feedback provision, thereby promoting motor control and learning theory best practice. Novel insights relevant to designing interactive systems for use within an elite sporting population are also discussed. This research presents an end-to-end strategy for the applied delivery of real-time feedback to skilled rowers bringing together engineering and social science disciplines. A land-based case series reveals that while statistically significant skill learning was not achieved, participants acquired sport specific technical awareness and heightened motivation as a result of the skills training intervention. Existing motor learning literature was tested as part of the study with a key finding being the lack of support for audible display of stroke acceleration through frequency modulation. Study limitations were identified that explain the lack of an effect of skills training on rower efficiency. The study also acted as a validation of the use of a land-based simulator to monitor and manipulate stroke velocity and a validation of the candidate feedback interfaces that had been implemented. As of result of this work, rowing coaches are able to evaluate their athletes in a novel way, achieving a deeper appreciation of their biomechanical efficiency. Upon identifying athletes with a need for technical development, coaches can intervene with the proposed methodology of skill development making use of the new technologies developed to deliver performance gains. This methodology would achieve enhanced validity through a deeper understanding of the reliability of the new metrics and their relationship to boat speed. Future attempts to test for skill learning should build upon the findings made in this work and, in due course, technology and theory should combine to deliver terminal feedback training during water-based rowing